Support slimming for single material based additive manufacturing. (August 2015) - Hu, Kailun; Jin, Shuo; Wang, Charlie C.L.
Abstract: In layer-based additive manufacturing (AM), supporting structures need to be inserted to support the overhanging regions. The adding of supporting structures slows down the speed of fabrication and introduces artifacts onto the finished surface. We present an orientation-driven shape optimizer to slim down the supporting structures used in single material-based AM. The optimizer can be employed as a tool to help designers to optimize the original model to achieve a more self-supported shape, which can be used as a reference for their further design. The model to be optimized is first enclosed in a volumetric mesh, which is employed as the domain of computation. The optimizer is driven by the operations of reorientation taken on tetrahedra with 'facing-down' surface facets. We formulate the demand on minimizing shape variation as global rigidity energy. The local optimization problem for determining a minimal rotation is analyzed on the Gauss sphere, which leads to a closed-form solution. Moreover, we also extend our approach to create the functions of controlling the deformation and searching for optimal printing directions. Graphical abstract: Highlights: Optimize the shape of a designed model into a 'self-supported' state for AM. Global shape of a model is preserved by minimizing the energy of rigidity. A closed-form solution for minimal rotation to drive the optimization. Tackle the shape optimization problem for reducing supporting structures.